2020
DOI: 10.1111/pde.14244
|View full text |Cite
|
Sign up to set email alerts
|

A case of pediatric lymphomatoid papulosis treated with photodynamic therapy and narrowband ultraviolet B

Abstract: Primary cutaneous CD30 + lymphoproliferative disorders (LPDs) are a spectrum of diseases of which lymphomatoid papulosis (LyP) is the most common. 1 Rarely, LyP can occur in children. 2 LyP is characterized by recurrent crops of papules and nodules that spontaneously resolve. 3 Half of patients experience symptoms of pain and/or pruritus. 4 The prognosis of LyP is excellent with a 10year overall survival of 92%. 5 LyP is associated with a 14%-51.7% risk of developing a second lymphoma, most commonly mycosis fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…These case reports showed therapeutic efficacy of PDT alone or in a combination of NB-UVB, including one pediatric case. [8][9][10] PDT only is effective to refractory lesions, as the authors observed and we experienced. Leg paralysis was observed in one patient after PDT, and the author conjectured that it might be due to nerve inflammation caused by free radicals production induced by PDT.…”
Section: Discussionsupporting
confidence: 64%
“…These case reports showed therapeutic efficacy of PDT alone or in a combination of NB-UVB, including one pediatric case. [8][9][10] PDT only is effective to refractory lesions, as the authors observed and we experienced. Leg paralysis was observed in one patient after PDT, and the author conjectured that it might be due to nerve inflammation caused by free radicals production induced by PDT.…”
Section: Discussionsupporting
confidence: 64%
“…In the first patient, a subsequent provocation skin test confirmed that the reaction was produced by the combination of MAL and illumination while in the second patient, provocation testing was not carried out due to the her young age ( Miguélez et al, 2013 ). No information regarding long-term safety of PDT in pediatric patients are available ( Snider et al, 2020 ). The main concern is the development of PDT-induced skin cancers, as reported in some cases in adult patients ( Borgia et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…He achieved the clearance of all lesions on his right arm within 2 months of combination therapy. Nevertheless, 2 years later new lesions appeared, but further PDT sessions were not attempted and subsequently the patient was lost at follow-up (Snider et al,. 2020).…”
Section: Cutaneous Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphomatoid papulosis is a chronic papulonecrotic or papulonodular skin disease and a rare form of indolent cutaneous T cell lymphoma characterized by crops of recurrent self-healing papules (2). PUVA-Bath photochemotherapy is associated with satisfactory results and along with topical corticosteroid therapy and methotrexate, are among the first-line therapies for this disease (52)(53)(54).…”
Section: Indications For Phototherapy In Dermatologymentioning
confidence: 99%